Issues of the legal category "duty" in the labor field - Zhumabayeva, A.B.; Kurennoy А.М.; Nurmagambetov А.М. (Bulletin of the Karaganda University “Law Series”, 2022)
The purpose of this article is to consider the issues of the place and role of legal categories in the system of law, the significance of the study of the category "duty" in labor law. The study of legal categories makes it possible to apply structured and systematic approaches in the methods of studying legal theoretical and legal concepts. The above method of cognition allowed the authors to come to the following conclusions and r e-sults. The category of obligation in relation to labor law is closely related to the mechanism of labor relations. Of particular difficulty is the development of a specific conceptual apparatus of the category of "duty" in la-bor law, since this category includes such concepts as "labor duties", "labor function", "duties in the field of work", "labor obligations", etc. "Obligation" as a legal category is undergoing significant changes, especially in the field of labor law. The country’s transition to a market economy, general democratization, openness and globalization of society, on the one hand, have given impetus to the dynamic development of all spheres of public and social life, and have determined a new vector for the development of labor relations based on free-dom of contractual relations. On the other hand, the growing influence of civil law, contractual elements of interaction between the employee and the employer leads to the fact that the fundamental categories, like “d u-ty” in the labor sphere, are gradually dissolving.